Impact of Cowpea-Based Food Containing Fish Meal Served With Vitamin C–Rich Drink on Iron Stores and Hemoglobin Concentrations in Ghanaian Schoolchildren in a Malaria Endemic Area - Egbi, G.; Ayi, I.; Saalia, F.K.; Zotor, F.; Adom, T.; Harrison, E.; Ahorlu, C.K.; Steiner-Asiedu, M. (Food and nutrition bulletin, 2015)
Background: Nutritional anemia is a public health problem among Ghanaian schoolchildren. There is need to employ dietary modification strategies to solve this problem through school and household feeding programs. Objective: To evaluate the effectiveness of cowpea-based food containing fish meal served with vitamin C-rich drink to improve iron stores and hemoglobin concentrations in Ghanaian schoolchildren. Methods: The study involved cross-sectional baseline and nutrition intervention phases. There were 150 participants of age 6 to 12 years. They were randomly assigned to 3 groups, fish meal -vitamin C (n = 50), vitamin C (n = 50), and control (n = 50), and given different cowpea-based diets for a 6-month period. Height and weight measurements were done according to the standard procedures, dietary data were obtained by 24-hour recall and food frequency questionnaire, hemoglobin concentrations were determined by Hemocue Hemoglobinometer, and serum ferritin and complement-reactive protein (CRP) were determined by enzyme-linked immunosorbent assay. Participants' blood samples were examined for malaria parasitemia and stools for helminthes using Giemsa stain and Kato-Katz techniques, respectively. Results: Mean ferritin concentration was not significantly different among groups. End line mean or change in hemoglobin concentrations between fish meal-vitamin C group (128.4 ± 7.2/8.3 ± 10.6 g/L) and control (123.1 ± 6.6/4.2 ± 10.4 g/L) were different, P < .05. Change in prevalence of anemia in fish meal-vitamin C group (19.5%) was different compared to those of vitamin C group (9.3%) and the control (12.2%). Levels of malaria parasitemia and high CRP among study participants at baseline and end line were 58% and 80% then 55% and 79%, respectively. Level of hookworm infestation was 13%. Conclusion: Cowpea-based food containing 3% fish meal and served with vitamin C-rich drink improved hemoglobin concentration and minimized the prevalence of anemia among the study participant (PDF) Impact of Cowpea-Based Food Containing Fish Meal Served With Vitamin C-Rich Drink on Iron Stores and Hemoglobin Concentrations in Ghanaian Schoolchildren in a Malaria Endemic Area. Available from: https://www.researchgate.net/publication/282045286_Impact_of_Cowpea-Based_Food_Containing_Fish_Meal_Served_With_Vitamin_C-Rich_Drink_on_Iron_Stores_and_Hemoglobin_Concentrations_in_Ghanaian_Schoolchildren_in_a_Malaria_Endemic_Area [accessed Sep 12 2018].
Keywords: fish meal; cowpea; iron stores; hemoglobin; anemia; Ghanaian schoolchildren; vitamin C–rich drink